Geography of religion, evangelical faith and space - Cruz, Diego Martins (Geosaberes; Vol 9 No 18 (2018): May - Aug., 2018)
This research seeks, through literature review to identify whether and how the available literature on Religion Geography provides grants to interpret the Gospel spatiality in Brazil, in order to understand the elements that make up the territorial expansion of faith seen in recent decades. Likewise, it seeks to show how the identity reinterpretation, cultural and outreach, elapsed in this medium, prefigure various forms of interpretation of the biblical text which in turn have repercussions on different forms of appropriation  and spatial cognition. It is noticed that the sacredness of the  space conditioned to the presence , perception and consensus of evangelical believers assumes a variable character overcomes materials and locational aspects to fit symbolic and subjective conformation space.